Same, but different? Testing monetary policy shock measures - Stephanie Ettmeier; Alexander Kriwoluzky (Economics Letters, 2019)
In this study, we determine the reliability and exogeneity of four popular monetary policy shock measures, namely the narrative series of Romer and Romer (2004), the high-frequency series of Barakchian and Crowe (2013), the high-frequency series of Gertler and Karadi (2015), and the hybrid series of Miranda-Agrippino and Ricco (2018b). To this end, we employ the Proxy-SVAR model and different empirical diagnostic tools to determine the shock measures' information content. We find that the measure of Miranda-Agrippino and Ricco (2018b), combining the insights from the narrative approach and high-frequency identification, outperforms the other three series.
Keywords: C12; C32; E32; E52; 330; Identification with external instruments; Monetary policy shock measures; Proxy-SVAR